“Os dois braços da boa medicina”: a medicina do corpo e da alma na obra de Francisco de Mello Franco - Stein, Tarcila Nienow (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation analyses the book written by the Brazilian physician Francisco de Mello Franco in 1794, titled Medicina Teológica ou súplica humilde feita a todos os Senhores Confessores, e Diretores, sobre o modo de proceder com seus Penitentes na emenda dos pecados, principalmente da Lascivia, Colera e Bebedice, focusing on the chapters that describe the soul disorders and on the recommended therapies and prescriptions for their healing. Mello Franco’s path is presented in the context of the changes that Portugal went through in the XVIII century, because of the Enlightenment and of the restructuring of the University of Coimbra. To better understand this period, documents such as 1772’s University of Coimbra Statute and Mello Franco’s private book collection catalogue were analysed, allowing for us to infer on the readings that the author might have done. It is worth mentioning that he had been arrested by the Portuguese Inquisition in 1781, which could be the reason for the anonymous publication of Medicina Teológica, since this book was dedicated to the clergy, intending their replacement by physicians on the treatment of the soul disorders. Two chapters are focused on the diseases described by Mello Franco, such as anger, melancholy, drunkenness, and lust related disorders. Other medical references, both modern and from the same period, were used in this dissertation. Before the XVIII century, soul disorders, such as those aforementioned, were associated with misbehaviour conducts and sins. In search for a cure, the sinners used to get help from the Church. With the Enlightenment, books as Mello Franco’s proposed an alternative, separating Faith and Science. The analytical approach chosen to this work is novel.
Keywords: Francisco de Mello Franco; Medicina teológica; Ilustração; Confessores; Doenças do ânimo; Enlightenment; Confessors; Soul disorders; ACCNPQ::Ciências Humanas::História